Revolutionizing hydrogen: Non-precious metals for sustainable water-based production - Walid Nabgan; Suhail Najm Abdullah; A.A. Jalil; B. Nabgan; M. Alhassan; A.A. Abdulrasheed; A.A. Fauzi; M.B. Bahari; Abdo M. Al-Fakih; N.M. Izzudin; M. Ikram; A.H.K. Owgi (Elsevier Ltd., 2025)
Hydrogen, a highly efficient and clean energy carrier, offers a promising alternative to fossil fuels, provided it's produced from renewable sources. Current methods of hydrogen production, primarily through high-temperature reforming of natural gas and petroleum, are energy-intensive and environmentally taxing. To tackle this, exploring alternative production techniques is imperative. One promising avenue is hydrogen generation from water, utilizing renewable energy surpluses. However, to make this approach cost-effective, efficient catalysts are essential. This review surveys various non-noble metals, supports, and methods for producing hydrogen and oxygen from water, aiming to identify gaps and recommend future research directions in non-noble catalyst development. Using bibliometric analysis, we discern trends and gaps in hydrogen production from water while also reviewing state-of-the-art electro-catalytic, photo-catalytic, and thermally driven water-splitting reactions. Challenges from previous research are highlighted, alongside prospects for future work, including the selection of cost-effective active metals and different catalyst manufacturing processes. The ultimate goal is to develop highly active catalytic systems that streamline water-splitting processes, thereby enabling economic and scalable hydrogen generation. This account provides insights and guidance for designing non-precious catalysts, contributing to the rational advancement of applied water-splitting systems.